Promotion rat race and public policy - Geir H. Bjertnæs (Statistics Norway, Research Department, 2012)
This study investigates whether excess effort to climb a career ladder justifies policy interventions. The answer depends on whether the government is able to levy a higher tax burden on career workers than on non-career workers. Both a tax on top income aimed at lowering the rewards of promotion and a labour law that restricts excess effort require such a differentiation in the tax burden to improve welfare. The differentiation in tax burden prevents that the welfare gain of reducing excess effort is neutralized by the welfare cost connected to an increase in the number of career workers.
Keywords: H21; H23; L22; J33; 330; Tournaments; Promotions; Status; Taxation